The Effect of Bank Size, Net Interest Margin, and Capital Adequacy Ratio on Commercial Banks’ Return on Assets: Empirical Evidence from Tanzania - Kessellie Traore Mulbah; Sinbad Kurbonov; Bobur Nasriddinov (European Scientific Journal, ESJ, 2024)
While the current body of literature offers valuable insights into the factors influencing bank financial performance, there is a significant paucity of empirical research focusing on least developed nations. This paper presents new evidence of the effect of bank size, capital adequacy ratio (CAR), and net interest margin (NIM) on banks’ return on assets (financial performance) from the perspective of Tanzania – a least-developed country. We employed the Random Effect, and the Generalized Least Squares (GLS) regression models utilizing a panel dataset spanning the period 2000 to 2022 of ten (10) Tanzanian commercial banks to examine the specific effect of the foregoing variables on commercial banks’ financial performance. The estimation results show that capital adequacy ratio (CAR) and bank size have positive significant effects on the financial performance of commercial banks in Tanzania. Whereas we found inconsistent results for the effect of NIM; while the random effect model shows a marginally significant positive effect on ROA, the GLS regression shows a significant negative effect, indicating that the effect of NIM could be either positive or negative depending on the context. Therefore, policymakers should prioritize measures aimed at promoting healthy levels of capital adequacy and encouraging the growth of larger banks while ensuring adequate oversight to mitigate potential risks associated with market dominance. Additionally, regulatory frameworks should be designed to foster competition and efficiency in the banking sector, facilitating a conducive environment for banks of all sizes to thrive and thus contribute to economic growth.